Competency of Rhizobial Inoculation in Sustainable Agricultural Production and Biocontrol of Plant Diseases - Kebede, Erana (Frontiers in Sustainable Food Systems, 2021)
The rate of growth of the global population poses a risk to food security, demanding an increase in food production. Much of the world's cultivable soils also do not have ideal farming conditions such as soil health and fertility problem and increased pest attacks, which are challenges of food production. In this perspective, there is a need to increase agricultural production using a more economically and environmentally sustainable approach. As practices of agricultural production and improvement, rhizobial inoculants represent a practically effective, ecologically safe, and economically alternative means of realizing maximum agricultural production. This review addressed how rhizobial inoculation advances agricultural production through improving plant growth, nutrient availability and uptake, and yields by enhancing bio-fixation of atmospheric nitrogen and solubilization of soil nutrients. Besides, rhizobial inoculants offer biocontrol of plant diseases by providing resistance against disease-causing pathogens or suppression of diseases. Mechanisms involved in biocontrol of plant diseases include competition for infection sites and nutrients, activation of induced systemic resistance, and production of substances such as growth hormones, antibiotics, enzymes, siderophores, hydrogen cyanide, and exo-polysaccharides. Consequently, this approach is promising as sustainable agricultural practices have yet to supplement or replace chemical fertilizers, serving as a basis for future research on sustainable agricultural production. Despite the multifunctional benefits of rhizobial inoculation, there is a variation in the implementation of this practice by farmers. Therefore, researchers should work on eradicating farmers' constraints in using rhizobia, and future studies should be concentrated toward the methods of improving inoculant quality and promotion of the technology.